2018
DOI: 10.1007/s00277-018-3361-2
|View full text |Cite|
|
Sign up to set email alerts
|

Real-world data on Len/Dex combination at second-line therapy of multiple myeloma: treatment at biochemical relapse is a significant prognostic factor for progression-free survival

Abstract: We evaluated progression-free survival (PFS) rate of patients treated with lenalidomide/dexamethasone (Len/Dex), the efficacy of the combination, and the prognostic significance of treatment at biochemical vs. clinical relapse on PFS in 207 consecutive myeloma patients treated with Len/Dex in second line, according to routine clinical practice in Greece. First-line treatment included bortezomib-based (63.3%) or immunomodulatory drug-based (34.8%) therapies; 25% of patients underwent autologous stem cell transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Another Greek study reported on a real-world population of relapsed MM patients uniformly treated with lenalidomide-dexamethasone (Rd) at second line in the current era. 16 The study demonstrated that presence of clinical relapse at treatment initiation negatively impacted post-progression PFS when compared with biochemical relapse. However, an important caveat was the lack of use of triplet regimens which are superior to doublets in relapsed MM.…”
Section: Discussionmentioning
confidence: 92%
“…Another Greek study reported on a real-world population of relapsed MM patients uniformly treated with lenalidomide-dexamethasone (Rd) at second line in the current era. 16 The study demonstrated that presence of clinical relapse at treatment initiation negatively impacted post-progression PFS when compared with biochemical relapse. However, an important caveat was the lack of use of triplet regimens which are superior to doublets in relapsed MM.…”
Section: Discussionmentioning
confidence: 92%
“…Biochemical relapse is defined by the IMWG as an increase in serum (absolute increase must be ≥0.5 g/dL) or urine M-protein (absolute increase must be ≥200 mg/24 h) ≥25% from the lowest response value, increased SFLC ratio ≥25% (absolute increase must be >10 mg/dL) from the lowest response value, increase of ≥10% of bone marrow plasma cells or increase in size of pre-existing bone lesions or plasmocytomas (Figure 1) [3]. Patients with confirmed biochemical relapse should receive therapy, especially in case of early, aggressive relapse, rapid increase in myeloma parameters and high-risk cytogenetics [19,33,34]. If the criteria of biochemical or clinical relapse are not met or in case of an asymptomatic, very slow increase in biochemical markers (evolving MM), close monitoring of myeloma parameters at least every 2-3 months is recommended [19,23].…”
Section: Indications To Initiate Therapymentioning
confidence: 99%
“…marrow plasma cells or increase in size of pre-existing bone lesions or plasmocytomas (Figure 1) [3]. Patients with confirmed biochemical relapse should receive therapy, especially in case of early, aggressive relapse, rapid increase in myeloma parameters and highrisk cytogenetics [19,33,34]. If the criteria of biochemical or clinical relapse are not met or in case of an asymptomatic, very slow increase in biochemical markers (evolving MM), close monitoring of myeloma parameters at least every 2-3 months is recommended [19,23].…”
Section: Choosing the Right Therapymentioning
confidence: 99%
“…At the 2014 meeting of the International Myeloma Working Group (IMWG), 9 relapse was subdivided into three categories: (1) clinical relapse, which is defined as reappearance of CRAB symptoms (hypercalcemia, renal impairment, anemia, or bone lesions); (2) paraprotein relapse, which is defined as re‐emergence of serum paraproteins (M protein); and (3) biochemical relapse, which is defined as M protein increases by ≥25% from the minimum value and an absolute level of increase by ≥500 mg/dl; it is recommended to initiate treatment at paraprotein relapse. In addition, recent clinical studies on relapsed and refractory MM (RRMM) have focused on initiating treatment at the first signs of biochemical relapse, resulting in excellent outcomes and suggesting it is important to initiate treatment changes at the earliest stages of disease progression 10 . However, the time to the increase in M‐protein levels is not defined in biochemical relapse, which may include various relapses of different durations from the best therapeutic effect to relapse, although there is currently no consensus recommendation to change therapy at this point.…”
Section: Introductionmentioning
confidence: 99%